Quality of life and objective functional impairment in lumbar spinal stenosis: a protocol for a systematic review and meta-analysis of moderators - Andrea Pozza; Fabio Ferretti; Anna Coluccia; Roberto Gusinu; Giacomo Gualtieri; Vitaliano Francesco Muzii (BMJ Open)
Background Lumbar spinal stenosis (LSS) is a common degenerative spine disease associated with a strong impairment in various quality of life areas, particularly the ability to perform work-related activity. Depression is a condition frequently associated. There is no comprehensive review on quality of life and objective functional impairment in LSS. This paper presents the protocol of the first systematic review and meta-analysis summarising evidence about quality of life and functional impairment in patients with LSS compared with healthy controls. Comorbid depressive disorders, age, gender, LSS duration, disability, pain severity and study methodological quality will be investigated as moderators.Methods The protocol is reported according to PRISMA-P guidelines. Studies will be included if they were conducted on patients aged 18 years old or older with primary LSS and if they reported data on differences in the levels of quality of life or objective functional impairment between patients with LSS and healthy controls. Independent reviewers will search published/unpublished studies through electronic databases and additional sources, will extract the data and assess the methodological quality. Random-effects meta-analysis will be carried out by calculating effect sizes as Cohen’s d indices. Heterogeneity will be examined by the I2 and the Q statistics. Moderators will be investigated through meta-regression.Conclusions A summary of the evidence on quality of life and functional impairment in LSS may suggest clinical and occupational health medicine strategies aimed to timely detect and prevent these outcomes. Higher percentages of patients with LSS with depression may be expected to be related to poorer quality of life. Depressive comorbidity might impact negatively on quality of life because it is associated with dysfunctional coping, disability and psychophysiological symptoms.Ethics and dissemination The current review does not require ethics approval. The results will be disseminated through publications in peer-reviewed journals.Review registration CRD42019132209.